Mendorong Inovasi Pendidikan Melalui Integrasi AI Dalam Pengembangan Pertanyaan HOTS (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
This training program aimed to enhance the skills of Tunas Jakasampurna School teachers in developing High Order Thinking Skills (HOTS) questions through the integration of artificial intelligence (AI). The training, involving 35 participants, utilized AI applications such as ChatGPT and Gemini to facilitate efficient question creation. Evaluation results showed a significant improvement in participants' understanding based on the comparison of pre-test and post-test scores. Participants appreciated the interactive approach that combined theoretical learning with hands-on practice. Recommendations include conducting similar training programs regularly with broader coverage and post-training support to ensure the sustainable application of AI in teaching activities.